Current knowledge on biotin nutrition in fish and research perspectives - Rodrigue Yossa; Pallab K. Sarker; Donald M. Mock; Santosh P. Lall; Grant W. Vandenberg (Reviews in Aquaculture, 2015)
Biotin, a water‐soluble vitamin, is essential for normal growth, development and health of all animals. In terrestrial animal nutrition, biotin has recently spurred scientific interest because of the increasing body of knowledge on biotin involvement in gene expression, cell cycle and reproduction in mammals, and recent advances in molecular biology techniques allowing a more effective estimation of biotin effects in metabolism and physiology. In contrast, this information is scarce in aquatic animal nutrition, as studies have essentially focused on the estimation of minimum biotin requirement for maximum growth and tissue storage as well as for the formulation of least‐cost diet. This scarcity of information is also due to the lack of well‐established indicators of biotin status in aquatic organisms. The present review is a comparative analysis of current knowledge on biotin physiology and nutritional biochemistry in terrestrial and aquatic animal nutrition. Also, general information on biotin sources, bioavailability, deficiency and requirement in mammals and fish is provided in order to plan further studies. In the future, biotin nutrition studies in aquaculture should also include haematological parameters, histopathology of the gills, liver and kidney, gonad development, gamete quality and quantity, fecundity, larvae survival and gene expression. Dietary biotin requirement levels should be estimated at every life history stage of farmed fish. The potential contribution of intestinal microflora to biotin supply in different fish species should be investigated. All this information will allow a better understanding of the essentiality of biotin in fish growth, development, reproduction and health.